Early vascular damage from smoking and alcohol in teenage years: the ALSPAC study. (28th August 2018) - Charakida, Marietta; Georgiopoulos, George; Dangardt, Frida; Chiesa, Scott T; Hughes, Alun D; Rapala, Alicja; Davey Smith, George; Lawlor, Debbie; Finer, Nicholas; Deanfield, John E
Abstract: Aims: To determine the impact of smoking and alcohol exposure during adolescence on arterial stiffness at 17 years. Methods and results: Smoking and alcohol use were assessed by questionnaires at 13, 15, and 17 years in 1266 participants (425 males and 841 females) from the ALSPAC study. Smoking status (smokers and non-smoker) and intensity ('high' ≥100, 'moderate' 20–99, and 'low or never' <20 cigarettes in lifetime) were ascertained. Participants were classified by frequency (low or high) and intensity of drinking [light (LI <2), medium (MI 3–9), and heavy (HI >10 drinks on a typical drinking day)]. Carotid to femoral pulse wave velocity (PWV) was assessed at 17 years [mean ± standard deviation and/or mean difference (95% confidence intervals)]. Current smokers had higher PWV compared with non-smokers ( P  = 0.003). Higher smoking exposure was associated with higher PWV compared with non-smokers [5.81 ± 0.725 vs. 5.71 ± 0.677 m/s, mean adjusted difference 0.211 (0.087–0.334) m/s, P  = 0.001]. Participants who stopped smoking had similar PWV to never smokers ( P  = 0.160). High-intensity drinkers had increased PWV [HI 5.85 ± 0.8 vs. LI 5.67 ± 0.604 m/s, mean adjusted difference 0.266 (0.055–0.476) m/s, P  = 0.013]. There was an additive effect of smoking intensity and alcohol intensity, so that 'high' smokers who were also HI drinkers had higher PWV compared with never-smokers and LI drinkers [mean adjusted increase 0.603 (0.229–0.978) m/s, P  = 0.002]. Conclusion: Smoking exposure even at low levels and intensity of alcohol use were associated individually and together with increased arterial stiffness. Public health strategies need to prevent adoption of these habits in adolescence to preserve or restore arterial health.